2013
DOI: 10.9745/ghsp-d-13-00055
|View full text |Cite
|
Sign up to set email alerts
|

Forest cover associated with improved child health and nutrition: evidence from the Malawi Demographic and Health Survey and satellite data

Abstract: In Malawi, net forest cover loss over time is associated with reduced dietary diversity and consumption of vitamin A-rich foods among children. Greater forest cover is associated with reduced risk of diarrheal disease. These preliminary findings suggest that protection of natural ecosystems could play an important role in improving health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 18 publications
3
80
0
2
Order By: Relevance
“…Despite compelling correlations between dietary quality and tree cover using coarse data (Johnson, et al 2013;Ickowitz et al 2014;Ickowitz et al 2016), individual case studies using better quality data have shown mixed effects. For example, it was found in the DRC that despite widespread consumption of wild edible plants, consumption levels were insignificant relative to other foods in the diet in terms of their contribution towards dietary adequacy for most nutrients (Termote et al 2012); a significant effect of the consumption of bushmeat in Madagascar on anaemia rates in children has been demonstrated (Golden et al 2011); and a comparison of the nutritional intake of bushmeat users and non-bushmeat users in tri-frontier region of Brazil, Peru and Columbia found diets of bushmeat users to be marginally higher in micronutrients (van Vliet et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite compelling correlations between dietary quality and tree cover using coarse data (Johnson, et al 2013;Ickowitz et al 2014;Ickowitz et al 2016), individual case studies using better quality data have shown mixed effects. For example, it was found in the DRC that despite widespread consumption of wild edible plants, consumption levels were insignificant relative to other foods in the diet in terms of their contribution towards dietary adequacy for most nutrients (Termote et al 2012); a significant effect of the consumption of bushmeat in Madagascar on anaemia rates in children has been demonstrated (Golden et al 2011); and a comparison of the nutritional intake of bushmeat users and non-bushmeat users in tri-frontier region of Brazil, Peru and Columbia found diets of bushmeat users to be marginally higher in micronutrients (van Vliet et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they may be important for the dietary quality of people living in proximity to forests (Blaney et al 2009;Golden et al 2011). Although few studies have quantified this contribution, recent evidence suggests that tree cover is positively associated with dietary diversity in Malawi (Johnson et al 2013) and in many other sub-Saharan African countries (Ickowitz et al 2014). While such studies suggest a link between forests and dietary quality, it is unclear whether such associations are due to forest-based agriculture, socialcultural and economic factors or the consumption of forest foods.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they found a positive association between the amount of land around a community characterized by 'medium' density tree cover (20-50 %) and frequency of consumption of vitamin-A rich fruit, green leafy vegetables, ASF, and 'other' fruits and vegetables. Johnson et al (2013) used DHS data from Malawi and found that children living in areas with more forest cover consumed more vitaminA-rich fruit, and that net forest loss was associated with less diverse diets. Using data for household level rather than village level forest cover in a study from Tanzania reported a relationship between multiple dietary diversity scores (1 and 7 day DDS and FVS) and tree cover within a 1.5 or 2 km radius of the home (Powell 2012).…”
Section: Forests and Tree-based Systemsmentioning
confidence: 99%
“…The contribution of agriculture to the dietary diversity of rural people, through food production pathways (Jones et al 2014) and income pathways (Sibhatu et al 2015), is relatively well understood. Several recent case studies from around the world have also found a positive association between proximity to forests and dietary diversity (Dounias and Froment 2006, Powell et al 2011, Johnson et al 2013, Ickowitz et al 2014. For example, using data from 21 African countries on children's diets (from USAID's Demographic Health Surveys) and tree cover (from MODIS data), Ickowitz et al (2014) found that children in Africa who lived in areas with more tree cover had more diverse and nutritious diets.…”
Section: Introductionmentioning
confidence: 99%